Preparation method of rare earth permanent magnet material and rare earth permanent magnet material

CN118098741BActive Publication Date: 2026-10-16NINGBO KETIAN MAGNET CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410378991.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-29
Publication Date
2026-10-16
Estimated Expiration
2044-03-29

AI Technical Summary

Technical Problem

如果磁体矫顽力高但是退磁曲线方形度差,这样的磁体不能满足要求的

Benefits of technology

[0065] The precursor powder Q has a B content of 0.85-0.90 wt.% and a Ga content of 0.3-0.8 wt.%. Due to the adoption of the above-mentioned technology, this invention has the following positive effects compared with the prior art:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118098741B_ABST
    Figure CN118098741B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a rare earth permanent magnet material and the rare earth permanent magnet material, and belongs to the technical field of rare earth permanent magnet materials. The preparation method comprises the following steps: S1, preparing precursor powders P and Q; S2, mixing the precursor powders P and Q according to a ratio of 30-50:50-70 to obtain a powder X; and S3, performing post-treatment on the powder X to obtain the rare earth permanent magnet material. The precursor powders P and Q both comprise RE, Al, Cu, Ga, Co, T, B and the balance of Fe. The B content of the precursor powder P is 0.93-0.95 wt.%, and the Ga content is 0.1-0.3 wt.%. The B content of the precursor powder Q is 0.85-0.90 wt.%, and the Ga content is 0.3-0.8 wt.%. The application obtains a magnet with high demagnetization curve squareness by preparing two kinds of precursor powders with different B content and Ga content, mixing the precursor powders, sintering and tempering after the mixing, and solves the problem of poor demagnetization curve squareness in a low-B high-Ga formula system, and meanwhile, the high coercivity characteristics of the magnet are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of permanent magnet materials, and specifically to a method for preparing rare earth permanent magnet materials. Background Technology

[0002] Sintered neodymium iron boron (NdFeB) permanent magnets, due to their high energy product and high coercivity, are key functional materials used in various fields such as electric vehicles, wind power generation, mobile communications, and intelligent robots. In recent years, with increasing operating temperatures and miniaturization requirements, the coercivity requirements for NdFeB magnets have become increasingly stringent. Coercivity represents a magnet's ability to resist external magnetic fields and temperature; higher coercivity indicates a greater resistance to external magnetic fields.

[0003] Neodymium iron boron (NdFeB) magnets have a polycrystalline structure, and their phases can be divided into a main phase and a grain boundary phase. Coercivity is mainly influenced by two factors: the coercivity within the magnet and the magnetocrystalline anisotropy field (H0) of the main phase (also known as the matrix phase). A The coercivity of magnets is positively correlated with their composition. On the other hand, it is influenced by the magnet's microstructure, primarily the grain boundary structure between two grains. A continuous distribution of non-magnetic grain boundaries, with wider boundaries, enhances demagnetization coupling, thus improving the magnet's coercivity. Of these two factors, HA is mainly affected by the magnet's composition; once the magnet's composition and formulation are determined, HA is also determined. The structure and organization of grain boundaries are closely related to the magnet's composition, especially the content of transition metal elements such as Al, Cu, and Ga, as well as boron (B), and also to the manufacturing process. Therefore, optimizing the composition, organization, and structure of grain boundaries becomes crucial for improving coercivity. While optimizing coercivity, the squareness of the magnet's demagnetization curve must also be considered, representing the consistency of the demagnetization process. If a magnet has high coercivity but poor squareness in its demagnetization curve, it will not meet the requirements.

[0004] To optimize grain boundaries, a common formulation system involves reducing the boron (B) content and increasing the gallium (Ga) content in the smelted alloy sheet. For example, the B content of the alloy sheet is around 0.92 wt.%, and the Ga content is around 0.6 wt.%, which is called a low-B, high-Ga formulation magnet. This type of magnet, by reducing the content of the main phase, forms a 6:13:1 phase at the grain boundaries, resulting in wide internal grain boundaries reaching 15 nm. Therefore, this type of magnet has relatively high coercivity, but its demagnetization curve squareness is poor. Typically, H... k / H cjBelow 92%, the overall coercivity of the magnet is still low. Uneven demagnetization within the magnet results in poor magnet consistency, particularly failing to meet high-temperature demagnetization resistance requirements. The main reason is excessive enrichment of the 6:13:1 phase, leading to high iron content at grain boundaries. (e.g., Formation of non-ferromagnetic grain boundary phase in a Ga-doped Nd-rich Nd–Fe–B sintered magnet, Scripta Materialia 113(2016)218–221). Optimizing the magnet structure and fabrication process in low-B formulation systems to achieve high coercivity while maintaining good squareness in the demagnetization curve remains a challenge for the industry. Summary of the Invention

[0005] This invention provides a method for preparing rare earth permanent magnet materials, and more particularly a method for preparing neodymium iron boron magnets.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing a rare-earth permanent magnet material, comprising:

[0008] S1: Preparation of precursor powder P and precursor powder Q;

[0009] S2: Mix the precursor powder P and the precursor powder Q in a weight ratio of 30-50:50-70 to obtain powder X;

[0010] S3: Perform post-processing on the powder X to obtain the rare earth permanent magnet material;

[0011] Among them, both precursor powder P and precursor powder Q include: RE, Al, Cu, Ga, Co, T, B, and the balance Fe;

[0012] Among them, RE is one or more of rare earth elements Pr, Nd, Ce, Dy, Ho, Ga, and Tb, RE includes at least Nd, and T is one or more of Ti, Zr, and Nb;

[0013] The precursor powder P has a B content of 0.93-0.95 wt.% and a Ga content of 0.1-0.3 wt.%.

[0014] The precursor powder Q has a B content of 0.85-0.90 wt.% and a Ga content of 0.3-0.8 wt.%.

[0015] In the above-mentioned method for preparing rare earth permanent magnet materials, the precursor powder P is a high-B, low-Ga powder, and the precursor powder Q is a low-B, high-Ga powder.

[0016] In the above-mentioned method for preparing rare earth permanent magnet materials, the precursor powder P is composed of RE. x Al y Cu z Ga m Co n T l B h Fe bal ;

[0017] The value of x ranges from 29 to 30.5 wt.%.

[0018] The value of y ranges from 0.05 to 0.15 wt.%.

[0019] The value of z ranges from 0.1 to 0.2 wt.%.

[0020] The value of m ranges from 0.1 to 0.3 wt.%.

[0021] The value of n ranges from 0.5 to 3 wt.%.

[0022] The value of l ranges from 0.1 to 0.2 wt.%.

[0023] The value of h ranges from 0.93 to 0.95 wt.%.

[0024] In the above-mentioned method for preparing rare earth permanent magnet materials, the precursor powder Q is composed of RE. α Al β Cu γ Ga δ Co θ T η B ω Fe bal ;

[0025] The value of α ranges from 30 to 32 wt.%.

[0026] The value of β ranges from 0.1 to 0.2 wt.%.

[0027] The value of γ ranges from 0.1 to 0.2 wt.%.

[0028] The value of δ ranges from 0.3 to 0.8 wt.%.

[0029] The value of θ ranges from 0.5 to 3 wt.%.

[0030] The value of η ranges from 0.1 to 0.2 wt.%.

[0031] The value of ω ranges from 0.85 to 0.90 wt.%.

[0032] In the above-mentioned method for preparing rare earth permanent magnet materials, in step S3, the post-processing includes:

[0033] S3.1: Stir the powder X;

[0034] S3.2: The powder X is pressed into a compact under a magnetic field to obtain a compact with a compact density of 4.4-4.6 g / cm³. 3 ;

[0035] S3.3: The pressed blank is sintered to obtain a raw magnet blank;

[0036] S3.4: Temper the blank magnet to obtain the rare earth permanent magnet material.

[0037] In the above-mentioned method for preparing rare earth permanent magnet materials, in step S3.1, the powder X is dispersed and stirred by airflow with an airflow pressure of 0.2-0.3 MPa and dispersed by argon gas flow.

[0038] In the above-mentioned method for preparing rare earth permanent magnet materials, in step S3.2, the powder X is filled into a magnetically conductive mold by adding it layer by layer, and after filling, it is pressed into shape under a magnetic field.

[0039] The above-mentioned method for preparing rare earth permanent magnet materials, wherein, in S1, the method for preparing the precursor powder P includes:

[0040] A1. Prepare raw material P;

[0041] A2: The raw material P is melted under vacuum at a temperature of 1470-1480℃, and then cooled to prepare a sheet P with a thickness of 0.25-0.35mm.

[0042] A3: The thin sheet P absorbs hydrogen and then dehydrogenates it at 500-550℃ to obtain coarse powder P with a diameter of 50-100μm;

[0043] A4: The coarse powder P is crushed by air jet milling to obtain the precursor powder P, wherein the average surface area particle size of the precursor powder P is 2.3-2.5 μm, and the maximum powder particle size of the precursor powder P is ≤6 μm.

[0044] The above-mentioned method for preparing rare earth permanent magnet materials, wherein, in S1, the method for preparing the precursor powder Q includes:

[0045] B1. Prepare raw material Q;

[0046] B2: The raw material Q is melted under vacuum at a temperature of 1440-1460℃, and then cooled to prepare a sheet Q with a thickness of 0.2-0.3mm.

[0047] B3: The thin sheet Q is subjected to hydrogen absorption, and then dehydrogenated at 400-450℃ to obtain coarse powder Q with a diameter of 50-100μm;

[0048] B4: The coarse powder Q is crushed by air jet milling to obtain the precursor powder Q, wherein the average surface area particle size of the precursor powder Q is 2.6-2.8 μm, and the maximum powder particle size of the precursor powder Q is ≤8 μm.

[0049] In the above-mentioned method for preparing rare earth permanent magnet materials, the particle size frequency distribution of the powder X has two peaks, with the first peak particle size at 2.5-3 μm and the second peak at 3.5-4 μm.

[0050] In the above-mentioned method for preparing rare earth permanent magnet materials, the grain boundary width of the rare earth permanent magnet materials is 9-12 nm.

[0051] In the above-mentioned method for preparing rare earth permanent magnet materials, the main phase grain size of the rare earth permanent magnet material is 3-4 μm, accounting for 50%, 6-8 μm, accounting for 35%, and below 3 μm, accounting for 15%.

[0052] In the above-mentioned method for preparing rare earth permanent magnet materials, the precursor powder Q is oxygenated by 40-60 ppm during the preparation process.

[0053] A rare-earth permanent magnet material, wherein it is obtained by the preparation method of the rare-earth permanent magnet material described in any one of the above claims, and the nominal composition of the rare-earth permanent magnet material is RE. a Al b Cu c Ga d Co e T f B g Fe bal ;

[0054] Among them, RE is one or more of rare earth elements Pr, Nd, Ce, Dy, Ho, Ga, and Tb, RE includes at least Nd, and T is one or more of Ti, Zr, and Nb;

[0055] The value of a ranges from 29 to 31 wt.%.

[0056] The value of b ranges from 0.05 to 0.5 wt.%.

[0057] The value of c ranges from 0.1 to 0.4 wt.%.

[0058] The value of d ranges from 0.1 to 0.4 wt.%.

[0059] The value of e ranges from 0.5 to 3 wt.%.

[0060] The value of f ranges from 0.1 to 0.2 wt.%.

[0061] The value of g ranges from 0.89 to 0.91 wt.%.

[0062] The demagnetization curve squareness H of the rare earth permanent magnet material k / H cj The percentage is 97-99.8%.

[0063] A rare earth permanent magnet material, comprising precursor powder P and precursor powder Q, wherein the weight ratio of the precursor powder P and the precursor powder Q is 30-50:50-70.

[0064] The precursor powder P has a B content of 0.93-0.95 wt.% and a Ga content of 0.1-0.3 wt.%.

[0065] The precursor powder Q has a B content of 0.85-0.90 wt.% and a Ga content of 0.3-0.8 wt.%. Due to the adoption of the above-mentioned technology, this invention has the following positive effects compared with the prior art:

[0066] (1) This invention prepares two precursor powders with different boron and Ga contents, then mixes the precursor powders, sintersects and tempers the mixture to obtain a magnet with high demagnetization curve squareness. This solves the problem of poor demagnetization curve squareness in low-B, high-Ga formulation systems, while also ensuring the high coercivity characteristics of the magnet. Attached Figure Description

[0067] Figure 1 This is a schematic diagram of the preparation method of the rare earth permanent magnet material of the present invention.

[0068] Figure 2 This is a comparison graph of the demagnetization curves of Embodiment 1 and Comparative Example 1 of the present invention. Detailed Implementation

[0069] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0070] In the description of this invention, it should be understood that the orientation or positional relationship indicated by terms such as "upper", "lower", "left", "right", "inner", "outer", "front", "rear", "lateral", and "vertical" are based on the orientation or positional relationship shown in the accompanying drawings and are only for the convenience of describing this invention, and are not intended to indicate or imply that the device or component referred to must have a specific orientation, and therefore should not be construed as a limitation of this invention.

[0071] It should be noted that the terms "horizontal" and "vertical" in this invention are used to describe approximate positional relationships, and not strictly "horizontal plane" or "vertical plane".

[0072] This embodiment provides a preferred method for preparing rare-earth permanent magnet materials, including:

[0073] S1: Preparation of precursor powder P and precursor powder Q.

[0074] S2: Mix precursor powder P and precursor powder Q in a weight ratio of 30-50:50-70 to obtain powder X.

[0075] S3: Post-process powder X to obtain rare earth permanent magnet materials.

[0076] Among them, the precursor powder P has the following composition: RE x Al y Cu z Ga m Co n T l B h Fe bal .

[0077] The value of x ranges from 29 to 30.5 wt.%.

[0078] The value of y ranges from 0.05 to 0.15 wt.%.

[0079] The value of z ranges from 0.1 to 0.2 wt.%.

[0080] The value of m ranges from 0.1 to 0.3 wt.%.

[0081] The value of n ranges from 0.5 to 3 wt.%.

[0082] The value of l ranges from 0.1 to 0.2 wt.%.

[0083] The value of h ranges from 0.93 to 0.95 wt.%.

[0084] Among them, the component of precursor powder Q is RE α Al β Cu γ Gaδ Co θ T η B ω Fe bal .

[0085] The value of α ranges from 30 to 32 wt.%.

[0086] The value of β ranges from 0.1 to 0.2 wt.%.

[0087] The value of γ ranges from 0.1 to 0.2 wt.%.

[0088] The value of δ ranges from 0.3 to 0.8 wt.%.

[0089] The value of θ ranges from 0.5 to 3 wt.%.

[0090] The value of η ranges from 0.1 to 0.2 wt.%.

[0091] The value of ω ranges from 0.85 to 0.90 wt.%.

[0092] Furthermore, as a preferred embodiment, in S3, the post-processing includes:

[0093] S3.1: Stir the powder X.

[0094] S3.2: Powder X is pressed into a compact under a magnetic field to obtain a compact with a compact density of 4.4-4.6 g / cm³. 3 .

[0095] S3.3: Sinter the pressed blank to make it dense, and obtain the blank magnet.

[0096] S3.4: Temper the blank magnet to obtain rare earth permanent magnet material.

[0097] Furthermore, as a preferred embodiment, in S3.1, the powder X is dispersed and stirred by airflow with an airflow pressure of 0.2-0.3 MPa, and argon gas is used for dispersion.

[0098] Specifically, the powder X is dispersed and mixed by an argon gas flow to improve the uniformity of the powder composition, thereby improving the squareness of the demagnetization curve of the magnet.

[0099] Specifically, by using airflow stirring, it is necessary to overcome the agglomeration force between ultrafine powders and ensure that the powder is evenly distributed between particles. This allows for the effective utilization of the grain boundary-rich phase in the precursor powder Q, which optimizes and encapsulates the grain boundaries of the precursor powder P.

[0100] Specifically, the airflow pressure is more suitable at 0.2-0.3 MPa. If the pressure is greater than 0.4 MPa, it will cause secondary breakage of the powder and result in the loss of rare earth-rich phases on the edge of the powder.

[0101] Specifically, the gas used is argon. During the stirring process, a small amount of heat is generated. This slight heating causes the rare earth-rich phase on the powder to react with nitrogen, resulting in nitriding of the grain boundary phase. This leads to a reduction in the liquid phase and a decrease in the squareness of the magnet.

[0102] Furthermore, as a preferred embodiment, in S3.2, powder X is filled into a magnetically conductive mold, added layer by layer, each layer being 1 mm thick. After filling, it is pressed into shape under a magnetic field. The pressing speed is 0.05 mm / s, the pressing pressure is 35-60 MPa, the demolding pressure is 5-10 MPa, and the compact density is 4.4-4.6 g / cm³. 3 .

[0103] Furthermore, as a preferred embodiment, in S3.3, the pressed blank is sintered to a dense state at a temperature of 1000℃-1050℃ for 2-10 hours to obtain a blank magnet.

[0104] Furthermore, as a preferred embodiment, in S3.3, during the tempering process, the first-stage tempering process is performed with a vacuum degree lower than 1*10. -2 Below Pa, hold at 700-900℃ for 3-5 hours; for secondary tempering, hold at 475-540℃ for 5 hours.

[0105] Preferably, the first-stage tempering process is performed under a vacuum degree lower than 1*10. -2 Below Pa, keep warm at 750℃ for 4 hours + 475*5 hours.

[0106] Preferably, the secondary tempering treatment is a heat treatment at 475°C for 5 hours.

[0107] Furthermore, as a preferred embodiment, in S1, the method for preparing the precursor powder P includes:

[0108] A1. Prepare raw material P according to the composition of the precursor powder P mentioned above.

[0109] A2: The raw material P is melted under vacuum at a temperature of 1470-1480℃. After melting, it is cooled in a copper mold to prepare a sheet P with a thickness of 0.25-0.35mm.

[0110] A3: Hydrogen is absorbed into thin film P, and then dehydrogenated at 500-550℃ to obtain coarse powder P of 50-100μm.

[0111] A4: The coarse powder P is crushed by air jet milling to obtain precursor powder P. The average surface area particle size of the precursor powder P is 2.3-2.5μm, and the maximum powder particle size of the precursor powder P is ≤6μm.

[0112] Furthermore, as a preferred embodiment, in S1, the method for preparing the precursor powder Q includes:

[0113] B1. Prepare raw material Q according to the composition of the precursor powder Q.

[0114] B2: The raw material Q is melted under vacuum at a temperature of 1440-1460℃. After melting, it is cooled in a copper mold to prepare a sheet Q with a thickness of 0.2-0.3mm.

[0115] B3: Hydrogen is absorbed into the thin sheet Q, and then dehydrogenated at 400-450℃ to obtain coarse powder Q of 50-100μm.

[0116] B4: The coarse powder Q is crushed by air jet milling to obtain precursor powder Q. The average surface area particle size of precursor powder Q is 2.6-2.8 μm, and the maximum powder particle size of precursor powder Q is ≤8 μm.

[0117] Furthermore, as a preferred embodiment, the particle size frequency distribution of powder X has two peaks, with the first peak particle size at 2.5-3 μm and the second peak at 3.5-4 μm.

[0118] Specifically, the two peaks mentioned above are mainly due to the mixing of precursor powder P and precursor powder Q. Precursor powder Q has more grain boundary phases, which effectively encapsulate the coarser precursor powder P with fewer grain boundary phases, resulting in the optimal structure: a slightly larger powder particle surrounded by smaller powder particles. This both inhibits grain growth and optimizes the distribution of grain boundaries.

[0119] Furthermore, as a preferred embodiment, the grain boundary width of the rare earth permanent magnet material is 9-12 nm.

[0120] Specifically, the grain boundary width of the magnet prepared from powder X is 7-15 nm, preferably 9-12 nm. The exchange coupling length of the main phase grains of the NdFeB magnet is 3 nm. For grain boundaries greater than 3 nm, the thinner and more continuous the grain boundaries, the better, as this is beneficial for improving coercivity and the squareness of the demagnetization curve. Generally, it is better to control it within 7-15 nm. The thicker the grain boundary, the higher the proportion of the grain boundary phase, which is not conducive to improving the remanence of the magnet. Within 7-15 nm, the magnet can maintain a good demagnetization coupling effect while optimizing the remanence of the magnet.

[0121] Furthermore, as a preferred embodiment, the main phase grain size of the rare earth permanent magnet material is 50% in the range of 3-4 μm, 35% in the range of 6-8 μm, and 15% in the range of less than 3 μm.

[0122] Furthermore, as a preferred embodiment, oxygen is added to the precursor powder Q at 40-60 ppm during the preparation process to appropriately increase the proportion of Nd2O3. Excessive oxides will reduce the squareness of the magnet, while an appropriate amount of oxides will increase the squareness of the magnet and the stability of the magnet.

[0123] Furthermore, this embodiment also provides a rare-earth permanent magnet material, which is obtained by the above-described method for preparing rare-earth permanent magnet materials, and its nominal composition is RE. a Al b Cu c Ga d Co e T f B g Fe bal .

[0124] RE is one or more of the rare earth elements Pr, Nd, Ce, Dy, Ho, Ga, and Tb, and RE includes at least Nd, while T is one or more of Ti, Zr, and Nb.

[0125] The value of a ranges from 29 to 31 wt.%, with the optimal range being 29.8 to 30.5 wt.%.

[0126] The value of b ranges from 0.05 to 0.5 wt.%, with the optimal range being 0.1 to 0.2 wt.%.

[0127] The value of c ranges from 0.1 to 0.4 wt.%, with the optimal range being 0.2 to 0.4 wt.%.

[0128] The value of d ranges from 0.1 to 0.4 wt.%, with the optimal range being 0.15 to 0.3 wt.%.

[0129] The value of e ranges from 0.5 to 3 wt.%, with the optimal range being 1 to 1.5 wt.%.

[0130] The value of f ranges from 0.1 to 0.2 wt.%, with 0.12 wt.%, 0.17 wt.%, and 0.2 wt.% being preferred.

[0131] The value of g ranges from 0.89 to 0.91 wt.%, with 0.89 wt.%, 0.90 wt.%, and 91 wt.% being preferred.

[0132] Furthermore, as a preferred embodiment, the squareness H of the demagnetization curve (second quadrant of the hysteresis loop) of this rare-earth permanent magnet material k / H cj The percentage is 97-99.8%.

[0133] Examples 1-3:

[0134]

[0135] Table 1

[0136] Please refer to Table 1, which shows the content parameters and corresponding performance parameters of precursor powder P and precursor powder Q in Examples 1 to 3.

[0137] Specifically, in Examples 1-3, precursor powder P (i.e., P1-P3 in Examples 1-3) was prepared according to the following method:

[0138] C1: Prepare raw material P according to the requirements in Table 1 (prepare raw material P for P1 to P3 separately), where the content of elements is by weight percentage. The total amount prepared is in the range of 100 kg, 600 kg, 800 kg and 1000 kg.

[0139] C2: The raw material P is melted under vacuum at a temperature of 1470-1480℃, and then cooled to prepare a sheet P with a thickness of 0.25-0.35mm.

[0140] C3: Hydrogen is absorbed into thin film P, and then dehydrogenated at 500-550℃ to obtain coarse powder P of 50-100μm.

[0141] C4: The coarse powder P is crushed by air jet milling to obtain precursor powder P (i.e., precursor powder P1 to P3 are obtained respectively). The average surface area particle size of the precursor powder P is 2.3-2.5μm, and the maximum powder particle size of the precursor powder P is ≤6μm.

[0142] Specifically, in Examples 1-3, precursor powder Q (i.e., Q1-Q3 in Examples 1-3) was prepared as follows:

[0143] D1: Prepare raw material Q according to the requirements in Table 1 (prepare raw material Q1 to Q3 separately), where the content of elements is by weight percentage. The total amount prepared is in the range of 100 kg, 600 kg, 800 kg and 1000 kg.

[0144] D2: The raw material Q is melted under vacuum at a temperature of 1440-1460℃, and then cooled to prepare a sheet Q with a thickness of 0.2-0.3mm.

[0145] D3: Hydrogen is absorbed into the thin sheet Q, and then dehydrogenated at 400-450℃ to obtain coarse powder Q with a diameter of 50-100μm.

[0146] D4: The coarse powder Q is crushed by air jet milling to obtain precursor powder Q (i.e., precursor powders Q1 to Q3 are obtained respectively). The average surface area particle size of the precursor powder Q is 2.6-2.8 μm, and the maximum powder particle size of the precursor powder Q is ≤8 μm.

[0147]

[0148]

[0149] Table 2

[0150] Please refer to Table 2, which shows the content parameters of powder X (i.e., X1 to X3) in Examples 1 to 3 and the performance parameters of the magnets prepared from powder X in Examples 1 to 3.

[0151] In Examples 1-3, powder X (i.e., X1-X3 in Examples 1-3) was prepared as follows:

[0152] E1: Mix precursor powder P and precursor powder Q at a weight ratio of 30-50:50-70 to obtain powder X (i.e. X1-X3 in Examples 1-3). The mixed powder and mixing ratio are detailed in Table 2.

[0153] E2: Powder X is dispersed and mixed by airflow with an airflow pressure of 0.2-0.3MPa. Argon gas is used for dispersion. Argon gas is used to prevent the agglomeration of powder particles. The agglomeration force between powder particles increases as the size of the powder decreases.

[0154] E3: Powder X is filled in a magnetically conductive mold, added layer by layer, each layer being 1mm. After filling, it is pressed into shape under a magnetic field. The pressing speed is 0.05mm / s, the pressing pressure is 35-60MPa, the demolding pressure is 5-10MPa, and the compact density is 4.4-4.6g / cm3.

[0155] E41: The pressed blank is sintered to a dense state at a sintering temperature of 1020-1050*(2-10)h to obtain a blank magnet.

[0156] E5: Temper the blank magnet. In the tempering process, the first-stage tempering process is to keep the vacuum degree below 1*10-2Pa at 700-900℃ for 3-5 hours, and the second-stage tempering process is to keep the temperature at 475-540℃ for 5 hours.

[0157] E6: The optimal tempering regime is 8*10-2 Pa, holding at 750℃ under vacuum for 4h + 475*5h, then purging with argon and rapidly cooling.

[0158]

[0159]

[0160] Table 3

[0161] Comparative Examples 1-3:

[0162] Please refer to Table 3, which shows the content parameters of powder D (i.e., D1 to D3) in Comparative Examples 1 to 3 and the performance parameters of the magnets prepared from powder D in Comparative Examples 1 to 3.

[0163] In Comparative Examples 1-3, magnets D (i.e., D1-D3 in Examples 1-3) were prepared as follows:

[0164] The finished magnet of Comparative Example 1 (D1) has the same final element ratio as the finished magnet in Example 1, but the preparation process is different. That is, it does not use two precursor powders to mix to obtain the final element ratio and prepare the magnet. Instead, it directly provides powder according to the final element ratio and prepares it according to the traditional process route of melting, hydrogen crushing, air jet milling, orientation molding, sintering and tempering.

[0165] Comparative Example 2 (D2) was prepared using precursor powders P2 and Q2, but the mixing ratio of the two was different from that of Example 2. The mixing ratio was 80% P2 + 20% Q2. The rest of the preparation method and the parameters involved in the preparation method were the same as those in Example 2.

[0166] Comparative Example 3 (D3) used the same powder as Example 3, namely 70% Q3 + 30% P3, but the powder was not subjected to airflow stirring and layer-by-layer addition to prepare the magnet.

[0167] Table 4

[0168] Analysis of Tables 1 to 4 above shows that Examples 1 to 3 prepared using the technical solution of the present invention have a reasonable average grain boundary width, which enables the magnet to maintain a good demagnetizing coupling effect, while optimizing the remanence and coercivity of the magnet.

[0169] refer to Figure 2 As can be seen from the data in Tables 1 to 4, Figure 2 The solid line in the figure represents the demagnetization curve of Example 1. Figure 2 The dashed line in the figure represents the demagnetization curve of Comparative Example 1. Examples 1 to 3 show that while the magnets achieve high coercivity, the demagnetization curves also exhibit better squareness. This demonstrates the use of two types of powder, P powder with high B and low Ga content.

[0170] When Q powder is mixed with low-B and high-Ga powder, compared with traditional processes such as Comparative Example 1, although the composition is the same, the coercivity and squareness of the demagnetization curve of the magnet are improved, indicating that the demagnetization consistency inside the magnet is improved. This is mainly due to the control of grain size, grain boundary width, and grain boundary phase composition in this process.

[0171] In addition, the P powder and Q powder in this invention also have a certain comparative effect. It can be seen that the P powder has low coercivity and it is difficult to obtain high anti-demagnetization, while the Q powder has high coercivity but low squareness.

[0172] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that those skilled in the art can make various modifications and improvements without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing a rare earth permanent magnet material, characterized in that, include: S1: Preparation of precursor powder P: A1. Prepare raw material P; A2: The raw material P is melted under vacuum at a temperature of 1470-1480℃, and then cooled to prepare a sheet P with a thickness of 0.25-0.35mm. A3: The thin film P absorbs hydrogen, and then dehydrogenates it at 500-550℃ to obtain 50-100 Coarse powder P; A4: The coarse powder P is subjected to air jet milling to obtain the precursor powder P, wherein the average particle size of the precursor powder P is 2.3-2.5 mm. The maximum particle size of the precursor powder P is ≤6. ;and Preparation of precursor powder Q: B1. Prepare raw material Q; B2: The raw material Q is melted under vacuum at a temperature of 1440-1460℃, and then cooled to prepare a sheet Q with a thickness of 0.2-0.3mm. B3: The thin film Q is subjected to hydrogen absorption, and then dehydrogenation is carried out at 400-450℃ to obtain 50-100 Coarse flour Q; B4: The coarse powder Q is subjected to air jet milling to obtain the precursor powder Q, wherein the average particle size of the precursor powder Q is 2.6-2.8 mm. The maximum particle size of the precursor powder Q is ≤8. ; S2: The precursor powder P and the precursor powder Q are mixed in a weight ratio of 30~50:50~70 to obtain powder X. The particle size frequency distribution of powder X has two peaks, with the first peak particle size being 2.5-3. The second peak is at 3.5-4 ; S3: Perform post-processing on the powder X to obtain the rare earth permanent magnet material; The precursor powder P is composed of RE. x Al y Cu z Ga m Co n T l B h Fe bal ; The value of x ranges from 29 to 30.5 wt.%. The value of y ranges from 0.05 to 0.15 wt.%. The value of z ranges from 0.1 to 0.2 wt.%. The value of m ranges from 0.1 to 0.3 wt.%. The value of n ranges from 0.5 to 3 wt.%; The value of l ranges from 0.1 to 0.2 wt.%; The value of h ranges from 0.93 to 0.95 wt.%. The precursor powder Q is composed of RE. α Al β Cu γ Ga δ Co θ T η B ω Fe bal ; The value of α ranges from 30 to 32 wt.%. The value of β ranges from 0.1 to 0.2 wt.%. The value of γ ranges from 0.1 to 0.2 wt.%. The value of δ ranges from 0.3 to 0.8 wt.%. The value of θ ranges from 0.5 to 3 wt.%. The value of η ranges from 0.1 to 0.2 wt.%. The value of ω ranges from 0.85 to 0.90 wt.%. Among them, RE is one or more of rare earth elements Pr, Nd, Ce, Dy, Ho, Ga, and Tb, RE includes at least Nd, and T is one or more of Ti, Zr, and Nb; The precursor powder P has a B content of 0.93-0.95 wt.% and a Ga content of 0.1-0.3 wt.%. The precursor powder Q has a B content of 0.85-0.90 wt.% and a Ga content of 0.3-0.8 wt.%.

2. The method for preparing rare earth permanent magnet materials according to claim 1, characterized in that, In S3, the post-processing includes: S3.1: Stir the powder X; S3.2: The powder X is pressed into a compact under a magnetic field to obtain a compact with a compact density of 4.4-4.6 g / cm³. 3 ; S3.3: The pressed blank is sintered to obtain a raw magnet blank; S3.4: Temper the blank magnet to obtain the rare earth permanent magnet material.

3. The method for preparing rare earth permanent magnet materials according to claim 2, characterized in that, In S3.1, the powder X is dispersed and stirred by airflow at a pressure of 0.2-0.3 MPa, and dispersed by argon gas flow.

4. The method for preparing rare earth permanent magnet materials according to claim 2, characterized in that, In S3.2, the powder X is filled into the magnetic mold by adding it layer by layer. After filling, it is pressed into shape under a magnetic field.

5. The method for preparing rare earth permanent magnet materials according to claim 1, characterized in that, The grain boundary width of the rare earth permanent magnet material is 9-12 nm. The main phase grain size of the rare earth permanent magnet material is 3-4. 50%, 6-8 35%, 3 The following accounts for 15%.

6. A rare earth permanent magnet material, characterized in that, It is obtained by the preparation method of rare earth permanent magnet material according to any one of claims 1 to 5, wherein the nominal composition of the rare earth permanent magnet material is RE. a Al b Cu c Ga d Co e T f B g Fe bal ; Among them, RE is one or more of rare earth elements Pr, Nd, Ce, Dy, Ho, Ga, and Tb, RE includes at least Nd, and T is one or more of Ti, Zr, and Nb; The value of a ranges from 29 to 31 wt.%. The value of b ranges from 0.05 to 0.5 wt.%. The value of c ranges from 0.1 to 0.4 wt.%; The value of d ranges from 0.1 to 0.4 wt.%. The value of e ranges from 0.5 to 3 wt.%. The value of f ranges from 0.1 to 0.2 wt.%. The value of g ranges from 0.89 to 0.91 wt.%. The demagnetization curve squareness H of the rare earth permanent magnet material k / H cj It is 97-99.8%.

Citation Information

Patent Citations

  • Alloy containing Ho and / or Gd, rare earth permanent magnet, raw material, preparation method and use

    CN110853857A

  • Neodymium-iron-boron magnet containing lanthanum and cerium and preparation method thereof

    CN112309662A